P86 Complete Sudden Recanalization: there is hope beyond the first pass effect. (29th August 2022) - Requena, M; García-Tornel, Á; Rodríguez, I; Olivé-Gadea, M; De Dios, M; Rodrigo, M; Rivera, E; Muchada, M; Piñana, C; Boned, S; Gramegna, LL; Rubiera, M; et al.
Abstract : Introduction: Achieving complete recanalization in a minimum number of attempts is the main procedural objective of mechanical thrombectomy. We aimed to explore the effect of the recanalization pattern in patients with final complete recanalization. Methods: We performed a retrospective analysis of patients with terminal carotid internal artery or M1-middle cerebral artery occlusion and complete recanalization (eTICI 2c-3) from 2014 in our center. Complete Sudden Recanalization (cSR) was considered when eTICI varied from 0–1 to 2c-3 without an interim partial recanalization step (2a or 2b) (progressive recanalization, PR). We explored the effect of cSR on clinical outcome compared with progressive complete recanalization. Results: Among four hundred patients with complete recanalization, in 301 was achieved with a cSR pattern. There were no differences between groups in terms demographic or clinical data and use of intravenous rtPA (42.2% vs 44.4%, p=0.69). The rate of terminal carotid artery occlusion (28.6% vs 44.4%, p=0.003), median number of passes (1 (IQR 1–2) vs 2 (2–3), p<0.001) and time from puncture to recanalization (27 (IQR 18–43) vs 46 (34–66) minutes; p<0.001) were lower in cSR group. At 90 days cSR was an independent predictor of good functional outcome (57.8% vs 44.4%, p=0.038). Compared with first pass effect, cSR after the first pass didn´t worsen the rate of good functional outcome (57.6% vs 58.6%, p=0.889). Conclusion: Among patients with a large vessel occlusion, the complete sudden recanalization pattern was a predictor of functional independence even when it did not occur in the first attempt. References: Zaidat OO, Castonguay AC, Linfante I, et al . First pass effect: a new measure for stroke thrombectomy devices. Stroke 2018 Mar;49 (3):660–666. DOI: 10.1161/Stroke AHA.117.020315. EPUB 2018 Feb 19. PMID: 29459390. García-Tornel Á, Rubiera M, Requena M, et al . Sudden recanalization: a game-changing factor in endovascular treatment of large vessel occlusion strokes. Stroke 2020 Apr;51 (4):1313–1316. DOI: 10.1161/Stroke AHA.119.028787. EPUB 2020 Feb 14. PMID: 32078495. Do you have any conflict of interest to declare? : No